Mushroom for the National Circular Economy - Pandey, Akhilesh Kumar; Rajan, Smita; Sarsaiya, Surendra; Jain, Sudhir Kumar (International Journal of Scientific Research in Biological Sciences, 2020)
Within the circular bio-economy, effective mushroom utilization through the key utilize of resources is fundamental in terms of producing profitable bioproducts, feasible improvement, and maximizing biological and socio-economic benefits. Commercial mushrooms are delivered on biowaste such as straw, saw tidy, and wood chips. As such, mushroom-forming fungi change over low-quality waste streams into high-quality food. Spent mushroom substrate (SMS) is ordinarily considered a waste material. Encourage investigation and advancement are required to create effective advances to empower the proficient exploitation of bioresources from mushroom. More prominent thought should be connected to vitality pathways to support such technologies. In this manner, there`s a request for development within the integrated approach in response to changing markets, and novel commercial models ought to be presented into the circular economy.